Bahaya Keterlibatan Hierarki Gereja dalam Politik Praktis - Ohoiledjaan, Joseph; Refo, Ignasius Samson Sudirman (Jurnal Seri Mitra (Refleksi Ilmiah Pastoral), 2024)
The purpose of this article is to explore the dangers of hierarchical involvement in practical politics and its impact on political stability, freedom of expression, and political participation of the community. The method used in this article is by using a qualitative approach with a library research method. This method will include an analysis of case studies and related literature. The results obtained from this article are the declining public trust in the church. The loss of reputation of the hierarchy in the church, which is independent and neutral in political affairs. The confusion in policy-making that has a negative impact on society. The prioritization of political interests and the abuse of church positions in their duty to teach justice and morality.